BUILDING THE PUBLIC ORGANIZATION BRAND BASED ON THE INTERNAL BRANDING PERSPECTIVE - Nurul Azizah; Arimurti Kriswibowo; Khusnul Khotimah; Rhea Ardhana (LPPM Universitas Djuanda Bogor, 2020)
A brand is the identity of an organization as well as the intangible asset that has significant added value for an organization. Currently, there are many organizations that are aware of the important role of brand for developing their organizations. Based on the internal branding concept, this research is aimed to gain the brand identity. The internal branding consists of three variables, namely brand orientation, brand knowledge, and brand involvement. The case was taken in Universitas Pembangunan Nasional (UPN)